PENGARUH COMMUNITY OF PRACTICE PADA IMPLEMENTASI KNOWLEDGE MANAGEMENT PADA KANTOR KELURAHAN REMPOA - Risza Putri Elburdah; Bulan Oktrima; Supardi Supardi; Styo Budi Utomo; Hestu Nugroho Warasto (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2020)
The purpose of community service is to implement one of Tri Dharma colleges. In addition, it is expected that with devotion to the community the existence of universities can contribute greatly to the development and application of scholarly to the community.This method of devotion implementation is done in several activities namely the survey stage that is socialization is done by arranging various things to be delivered during the dedication activities that will be conducted which include: the preparation of materials that will be given, drafting the awarding schedule, the division of tasks of devotion teams and surveys to the location of devotion. Socialization stage is before the dedication activities carried out first conducted socialization stage is doing a relationship with the chief, convey the intent and purpose of this devotion. At this stage is also done cooperation and determine the schedule of the dedication activities. The team of community dedication activities is the Faculty of Economics lecturer in management as many as 5 people. The dedication team provides material about patchwork The Influence of Community of Practice on the implementation of Knowledge Management at Kantor Kelurahan Rempoa.